2010
DOI: 10.2139/ssrn.1679785
|View full text |Cite
|
Sign up to set email alerts
|

Weight of the Crisis: Evidence from Newborns in Argentina

Abstract: We investigate how birth weight in Argentina responds to monthly economic ‡uctuations around the economic collapse of December 2001, and document its procyclicality with respect to the month of birth during [2001][2002][2003]. Our data reveal that this procyclicality is driven by children born to low-educated mothers. We exploit the fact that the impacts of maternal nutrition and stress on birth weight vary according to the stages of gestation. We …nd evidence that the birth weights of children to loweducated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 47 publications
2
43
4
Order By: Relevance
“…Other studies (e.g., Evans et al, 2007) considered that the direct impact of maternal stress on birth weight disappears after controlling for confounding factors (unhealthy behaviours). Maternal stress has been considered the most important determinant of gestational length (and prevalence of preterm deliveries and LBW) in the first trimester of gestation, while foetal growth (and the prevalence of intrauterine growth restriction) depends more on resources and material conditions-particularly maternal nutrition-in the third trimester (Bozzoli and Quinta-Domeque, 2014). According to this hypothesis, maternal physiology would dampen the negative consequences of stress as pregnancy progresses, with little impact in the final stage of pregnancy (de Weeth and Buitelaar, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (e.g., Evans et al, 2007) considered that the direct impact of maternal stress on birth weight disappears after controlling for confounding factors (unhealthy behaviours). Maternal stress has been considered the most important determinant of gestational length (and prevalence of preterm deliveries and LBW) in the first trimester of gestation, while foetal growth (and the prevalence of intrauterine growth restriction) depends more on resources and material conditions-particularly maternal nutrition-in the third trimester (Bozzoli and Quinta-Domeque, 2014). According to this hypothesis, maternal physiology would dampen the negative consequences of stress as pregnancy progresses, with little impact in the final stage of pregnancy (de Weeth and Buitelaar, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of monthly data for these economic indicators in Spain does not allow us to perform an analysis of the timing of exposure to economic fluctuations by trimesters of pregnancy as Bozzoli and Quinta-Domeque (2014) confirmed that all independent variables were predictors of underweight at birth risk, and that there were no significant interactions on underweight at birth risk among them. Figure 1 shows the trend in the prevalence of underweight at birth by month and year of birth, both for the original series and for the estimated trend component on a seasonally adjusted series (see Table I [FIGURE 1] Table I [FIGURES 2 to 6]…”
mentioning
confidence: 99%
“…Studies from developed countries, the U.S. in particular, showed that recessions can be "good for your health" (Ruhm, 2000;Chay and Greenstone, 2003;Dehejia and Lleras Muney, 2004). In contrast, most studies from developing countries showed that child health is procyclical (Paxson and Schady, 2005 for Peru; Bhalotra, 2010 for India; Cruces et al, 2012 andBozzoli andQuintana-Domeque, 2014 for Argentina; Baird et al, 2011 for a large set of developing countries); an obvious exception is the study of Miller and Urdinola (2010) where they show that infant mortality increases with income in Colombia. The evidence from middle-income countries is mixed (Schady and Smitz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…8 The last three papers are part of a broader economics literature that uses quasi-experiments to investigate how a pregnant woman's environment affects the fetus. Economists have made important contributions by considering a wide range exposures (Almond and Currie 2011), which include economic crises and shocks, (Dehejia and LlerasMuney 2004;Banerjee et al 2010;Bozzoli and Quintana-Domeque 2010;Burlando 2011), policy changes (Baker 2008;Almond et al 2009b;Chung and Kim 2011), school openings (Currie and Moretti 2003), epidemics (Almond and Mazumder 2005;Almond 2006;Mazumder et al 2010), pollution Almond et al 2009a;Currie and Walker 2011;, and climate change (Deschênes et al 2009). 1993,2003).…”
mentioning
confidence: 99%